A Comparative Review of Chemotherapy-Induced Peripheral Neuropathy in In Vivo and In Vitro Models. (January 2020) - Eldridge, Sandy; Guo, Liang; Hamre, John
Chemotherapy-induced peripheral neuropathy (CIPN) is an adverse effect caused by several classes of widely used anticancer therapeutics. Chemotherapy-induced peripheral neuropathy frequently leads to dose reduction or discontinuation of chemotherapy regimens, and CIPN symptoms can persist long after completion of chemotherapy and severely diminish the quality of life of patients. Differences in the clinical presentation of CIPN by widely diverse classifications of anticancer agents have spawned multiple mechanistic hypotheses that seek to explain the pathogenesis of CIPN. Despite its clinical relevance, common occurrence, and extensive investigation, the pathophysiology of CIPN remains unclear. Furthermore, there is no unequivocal gold standard for the prevention and treatment of CIPN. Herein, we review in vivo and in vitro models of CIPN with a focus on histopathological changes and morphological features aimed at understanding the pathophysiology of CIPN and identify gaps requiring deeper exploration. An elucidation of the underlying mechanisms of CIPN is imperative to identify potential targets and approaches for prevention and treatment.